Investigation of modified nanopore arrays using FIB/SEM tomography - Holzinger, A.; Neusser, G.; Austen, B.; Gamero-Quijano, A.; Herzog, G.; Arrigan, Damien; Ziegler, A.; Walther, P.; Kranz, C. (R S C Publications, 2018)
The investigation of electrochemical processes at the interface of two immiscible electrolyte solutions (ITIES) is of great interest for sensing applications, and serves as a surrogate to the study of biological transport phenomena, e.g. ion channels. Alongside e-beam lithography, focused ion beam (FIB) milling is an attractive method to prototype and fabricate nanopore arrays that support nanoITIES. Within this contribution, we explore the capability of FIB/scanning electron microscopy (SEM) tomography to visualize the actual pore structure and interfaces at silica-modified nanoporous membranes. The nanopores were also characterized by atomic force microscopy (AFM) using ultra-sharp AFM probes to determine the pore diameter, and using scanning transmission electron microscopy (STEM) and energy dispersive X-ray (EDX) spectroscopy, providing additional information on the elemental composition of deposits within the pores. Si-rich particles could be identified within the pores as well as at the orifice that had faced the organic electrolyte solution during electrochemical deposition. The prospects of the used techniques for investigating the interface at or within FIB-milled nanopores will be discussed.